Automated Teller Machine (ATM)- A “Pathogen City” – A surveillance Report from Locations in and around Madurai City, Tamil Nadu, India - Chellappa Mabel Joshaline; Subathra M.; Shyamala M.; Padmavathy S.; Rekha Rekha (International Journal of Public Health Science (IJPHS), 2014)
ATM is used by millions of people in a day. It is meant to be a public utility device.Hence the microorganism’s plays a major role in accommodating the safer place, ATM.Hence to this account an elaborate survey was taken for complete assessment of microbiology in and around Madurai city. Swabs were collected from each ATM screen, buttons, floor, user’s hand, exposure of plates and also extended the work in relation with microorganisms prevalent in ladies toilet the samples collected from ATM were plated in nutrient agar plates. The results showed the presence of increased bacterial count subsequently, most pathogens on characterization extended revealed the genus of the particular organism E-coli, Pseudomonas, Staphylococcus aures, Klebsiella, Micrococcus, Salmonella, Serratia and fungal species included Aspergillus sp, Mucor sp and Fusarium. Antibiogram study of bacteria also provides us information about the antibiotic resistance pattern of the bacterial isolates.